If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 = 4x + -6 Reorder the terms: -15 + 6x = 4x + -6 Reorder the terms: -15 + 6x = -6 + 4x Solving -15 + 6x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + 6x + -4x = -6 + 4x + -4x Combine like terms: 6x + -4x = 2x -15 + 2x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + 2x = -6 + 0 -15 + 2x = -6 Add '15' to each side of the equation. -15 + 15 + 2x = -6 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = -6 + 15 2x = -6 + 15 Combine like terms: -6 + 15 = 9 2x = 9 Divide each side by '2'. x = 4.5 Simplifying x = 4.5
| -3(9+4x)=-111 | | v=.33*256*17 | | 4x+22=12x+4 | | 17=x-1 | | -5(-1x+1)=35 | | 2x^2+4x+15=0 | | 4x+5+6x=-105 | | 4x+5+6x=-112 | | 4x+5+6x= | | 1/2= | | 6*x+4x+2x+2x+2x=900000 | | 24+x*5=4.14*(6+x) | | x^2+x*2+3=6 | | 24=-x+5x-4 | | 3x=7x-5 | | 3x-5=7X | | -1+3x+3x=5 | | 2c^2+7C+3= | | (2x-3)-9=0 | | 8(x-8)=2x-8 | | 3x+7+7x=37 | | 48-4x=5x+18 | | y=4x^2-5 | | 16s*16s+56s+49=0 | | 756845628-589= | | 8x+(5x-6-4x+1)=4x+(4x-1) | | 3x+6y= | | -111-77x=8x+24 | | (-4)-6x=-52 | | 12x-15=7x+50-7x | | 7(x-6)=6x-49 | | 5(x+1)=3 |